2023
DOI: 10.1111/wvn.12630
|View full text |Cite
|
Sign up to set email alerts
|

An integrative review of factors and interventions affecting the well‐being and safety of nurses during a global pandemic

Abstract: Background Nurses experienced physical and mental exhaustion during the COVID‐19 pandemic. Understanding the impact of the pandemic on nurses and effective strategies to support them is critical for increasing nurse resilience and reducing burnout. Aims The aims of this study were (1) to synthesize the literature examining how factors associated with the COVID‐19 pandemic affected the well‐being and safety of nurses (2) and to review interventions which may promote nurse mental health during crises. Methods Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In addition, many nurses reported a lack of visible and supportive leadership in healthcare organizations that contributed to increases in anxiety, stress, depression, and moral distress. These findings highlight the importance of implementing comprehensive support mechanisms and effective leadership strategies to address mental health challenges faced by nurses during crises [19] . Similarly, a meta-analysis of 401 studies, which involved 458,754 participants in 58 countries [20] , revealed the following aggregate prevalence rates among hospital HCW: depression at 28.5%, anxiety at 28.7%, post-traumatic stress disorder (PTSD) at 25.5%, alcohol and substance use disorder at 25.3%, and insomnia at 24.4%.…”
Section: Discussion and Resultsmentioning
confidence: 89%
“…In addition, many nurses reported a lack of visible and supportive leadership in healthcare organizations that contributed to increases in anxiety, stress, depression, and moral distress. These findings highlight the importance of implementing comprehensive support mechanisms and effective leadership strategies to address mental health challenges faced by nurses during crises [19] . Similarly, a meta-analysis of 401 studies, which involved 458,754 participants in 58 countries [20] , revealed the following aggregate prevalence rates among hospital HCW: depression at 28.5%, anxiety at 28.7%, post-traumatic stress disorder (PTSD) at 25.5%, alcohol and substance use disorder at 25.3%, and insomnia at 24.4%.…”
Section: Discussion and Resultsmentioning
confidence: 89%
“…Internationally, healthcare workers left jobs or reduced hours for multiple reasons, including illness, fear of infecting themselves or loved ones with COVID-19, needing to care for children and other family members, and the effects of extended heavy workloads. (1–3) Those who stayed at work also experienced persistent negative impacts, with one international review identifying consequences such as losing hope or professional identity,(4) which have led to persistent workforce shortages. )…”
Section: Introductionmentioning
confidence: 99%
“…Emergency departments (EDs) are critical high-stake environments within the healthcare system [1], where the pace is relentless and the margin for error is minimal [2,3]. Tese units serve as the central hub for acute treatment, where decisions must be rapid and precise [4][5][6], with the potential to signifcantly alter patient outcomes [3]. Te intensity and pressure inherent in emergency departments require a leadership style that not only facilitates rapid decision-making but also nurtures a supportive and cohesive team environment [7,8].…”
Section: Introductionmentioning
confidence: 99%